Ultrasensitive graphene optoelectronic probes for recording electrical activities of individual synapses - Wang, Rui (Nano Lett, 2018)
The complex neuronal circuitry connected by sub-micron synapses in our brain calls for technologies that can map neural networks with ultrahigh spatiotemporal resolution to decipher the underlying mechanisms for multiple aspects of neuroscience. Here we show that through combining graphene transistor arrays with scanning photocurrent microscopy, we can detect the electrical activities of individual synapses of primary hippocampal neurons. Through measuring the local conductance change of graphene optoelectronic probes directly underneath neuronal processes, we are able to estimate millivolt extracellular potential variations of individual synapses during depolarization. The ultrafast nature of graphene photocurrent response allows for decoding of activity patterns of individual synapses with a sub-millisecond temporal resolution. This new neurotechnology provides promising potentials for recording of electrophysiological outcomes of individual synapses in neural networks.